Determining of the Hydroxyurea Effluence on TCD Parameters of Sickle Cell Patients - Nasser Sharafadinzadeh; Nastaran Majdinasb; Khodamorad Zandian; Keiwan Taherpoor; Armaghan Moravej Aleali; Mohamad Pipelzadeh (مجله دانشکده پزشکی اصفهان, 2009)
Background: Sickle cell disease is the most common hemoglobinopathies that affect a specific intracellular protein named as hemoglobin. This disease has several clinical manifestations including, CNS involvement. Stroke is one of the most important manifestations of this disease. Diagnosis of high risk patient and necessary intervention as transfusion can reduce its complications, but its effects on TCD parameters remain undefined. The aim of this study was to show the efficacy of hydroxyurea in decreasing of velocity parameter in sickle cell disease. Methods: 25 Sickle cell Patients who had indication of hydroxyurea treatment were selected for the study and at the first of the study, total hemoglobin, hemoglobin s, hemoglobin F and peak systolic velocities of middle cerebral and internal carotid arteries was measured and then repeated 6 month later. Findings: 25 Patients (18 male and 7 female) between 3 to 47 years old and by the mean of ages 16.5 years old were evaluated. Our data showed significant changes of mean hemoglobin, hemoglobin S, hemoglobin F and peak systolic velocities of middle cerebral and internal carotid arteries before and after 6 month hydroxyurea treatment (P < 0.05). Conclusion: Our Study Suggests that hydroxyurea can improve hemoglobin state and reduce peak systolic velocities of middle cerebral and internal carotid arteries. Key words: Sickle cell disease, Hydroxyurea, Transcranial doppler ultrasonography.